2020
DOI: 10.1111/ene.14557
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hypertension in multiple sclerosis based on 37 million electronic health records from the United States

Abstract: Background and purposeHypertension (HTN) is a common comorbidity in multiple sclerosis (MS), and it significantly contributes to adverse outcomes. Unfortunately, the distribution of HTN in persons with MS has not been well characterized, and prior estimates have primarily relied on modest sample sizes. The objective of this study was to robustly describe the distribution of HTN in the MS population in comparison to the non‐MS population with considerations for age, sex, and race. To date, this is the largest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…15 Higher prevalence of hypertension in PwMS compared to MS-free individuals and its increasing tendency during MS was also confirmed in the US study, based on the electronic health records of 37 million US citizens. 16 In line with our findings, Marrie et al showed that the presence of one or more vascular comorbidities (hypertension, hypercholesterolemia, diabetes, heart disease, and peripheral vascular disease) in PwMS was associated with a 6-year faster progression to a disability level requiring an ambulatory assistance. 4 An increased risk for disability progression was also observed if one or more vascular comorbidities were present at the time of MS diagnosis and the risk increased with a rising number of vascular comorbidities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…15 Higher prevalence of hypertension in PwMS compared to MS-free individuals and its increasing tendency during MS was also confirmed in the US study, based on the electronic health records of 37 million US citizens. 16 In line with our findings, Marrie et al showed that the presence of one or more vascular comorbidities (hypertension, hypercholesterolemia, diabetes, heart disease, and peripheral vascular disease) in PwMS was associated with a 6-year faster progression to a disability level requiring an ambulatory assistance. 4 An increased risk for disability progression was also observed if one or more vascular comorbidities were present at the time of MS diagnosis and the risk increased with a rising number of vascular comorbidities.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent Australian study, it was observed that the highest increase among comorbidities in the prevalence from disease onset to the time of investigation (on average 20.5 years after the disease onset) was found for hypertension (+21.9%) and hypercholesterolemia (+16.3%) 15 . Higher prevalence of hypertension in PwMS compared to MS‐free individuals and its increasing tendency during MS was also confirmed in the US study, based on the electronic health records of 37 million US citizens 16 . In line with our findings, Marrie et al showed that the presence of one or more vascular comorbidities (hypertension, hypercholesterolemia, diabetes, heart disease, and peripheral vascular disease) in PwMS was associated with a 6‐year faster progression to a disability level requiring an ambulatory assistance 4 .…”
Section: Discussionmentioning
confidence: 60%
“…Forty-one percent of persons with MS in the United States may have a HTN diagnosis, including 53% of Black Americans with MS. 3 Unfortunately, HTN is associated with adverse MS outcomes, which is likely dependent on the evolution of overlapping and/or distinct disease processes-this presents challenges for characterizing their relationship. However, there are opportunities to advance our understanding of key aspects, such as HTN AAO in those with/at risk for MS and those without MS. We observed no differences in HTN AAO by MS status, nor differences by sex or in White or Black Americans.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In multiple sclerosis (MS) patients, the burden of HTN and CVD is significantly higher than that in non-MS patients. 3,4 CVD is also a leading cause of death in MS, and these CVD mortality rates are much higher than those in the general population. 5 Given the relationships between HTN and CVD in MS, HTN AAO on CVD and CVD mortality, and CVD mortality in MS, we hypothesized that there may be an association between HTN AAO in MS, which may in part explain the elevated risk for CVD mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Essential hypertension (EH), accounting for 90–95% of the total hypertension cases [ 1 ], is a polygenic disease. Genetic alterations, environmental factors, and gene-environmental interactions are supposed to have a key role in the etiology of EH [ 2 ].…”
Section: Introductionmentioning
confidence: 99%